Internet-based cognitive behavioural therapy for adults with tinnitus in the UK: study protocol for a randomised controlled trial - Peter M Allen; David M Baguley; Gerhard Andersson; Eldré W Beukes; Vinaya Manchaiah (BMJ Open)
Introduction Tinnitus is one of the most distressing hearing-related symptoms. Innovative ways of managing tinnitus distress and the related healthcare burden of treating tinnitus are required. An internet-based cognitive behavioural therapy (iCBT) intervention has been developed in Sweden to improve access to evidence-based tinnitus treatments. This study aims to determine the feasibility and effectiveness of iCBT in reducing the impact associated with tinnitus, in the UK. It, furthermore, aims to establish whether there are subgroups of tinnitus sufferers for whom this iCBT intervention may be more suitable.Methods and analysis A two-armed randomised control trial—with a 1-year follow-up design—will be used to evaluate the effectiveness of iCBT on tinnitus distress. A delayed treatment design using a weekly check-in control group will be used. 70 participants will be randomly assigned to each group by an independent researcher by using a computer-generated randomisation schedule, and after being prestratified for age and tinnitus severity. They will undergo the iCBT e-health intervention online together with audiological therapeutic support. The main outcome measure is the Tinnitus Functional Index. Process evaluation of the intervention will also be conducted. Data analysis will be in accordance with Consolidated Standards of Reporting Trials guidelines.Ethics and dissemination Ethical approval has been granted. If this intervention proves effective, it may be possible that at least some tinnitus sufferers can be managed though an iCBT e-learning treatment programme. This would be cost effective and potentially will free up services for those with more severe problems that need face-to-face treatment.Trial registration number ClinicalTrials.gov; NCT02370810, date 05/03/2015.